Melatonin may Regulate Apoptotic Pathway via Affecting Bax, Bcl2I1 and XIAP Levels in Myocardial Ischemia-Reperfusion Injury - Aslan, Gulnur; Sahna, Engin (Karger, 2021)
[Abstract Not Available]
Keywords: Melatonin; ischemia-reperfusion injury; apoptosis; Bax; Bcl2I1; XIAP